Proses Bunker Kapal Tb. Patria pada PT. Snepac Agency Asia Molawe - Ariya Ananta; Dirhamsyah Dirhamsyah; Dina Rispianti (Jurnal Transformasi Bisnis Digital, 2025)
Refueling or bunkering is an activity carried out when the ship is ready to sail. In refueling activities, it is very dangerous for work accidents to occur, the implementation of refueling (bunkers) which is less than optimal can also cause accidents and losses for the company and other parties. These losses include oil spilling into the sea, fires and so on. The execution of refueling is still less than optimal in using personal protective equipment and there is a lack of coordination between several crew members. The aim of this research is to determine the causes of work accidents, efforts are being made to improve supervision of refueling on ships. Supervision during the fuel oil filling process is very important because this activity carries a very high risk of work accidents. This method was written using field methods (field research), namely observation and interviews (interviews) and literature (Library Research). Factors that cause work accidents during the process of filling ships with fuel oil on ships are lack of coordination between the officers involved, lack of awareness in the use of personal protective equipment in accordance with SOP (Standard Operational Procedure)..